2005
DOI: 10.2174/1568011053174828
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Properties of Neem Leaves: A Review

Abstract: Azadirachta indica, commonly known as neem, has attracted worldwide prominence in recent years, owing to its wide range of medicinal properties. Neem has been extensively used in Ayurveda, Unani and Homoeopathic medicine and has become a cynosure of modern medicine. Neem elaborates a vast array of biologically active compounds that are chemically diverse and structurally complex. More than 140 compounds have been isolated from different parts of neem. All parts of the neem tree- leaves, flowers, seeds, fruits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
296
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(303 citation statements)
references
References 48 publications
5
296
0
2
Order By: Relevance
“…Several studies have shown that inclusion of HFA in broiler diet improves performance, enhances feed utilization and promotes gut health of broiler without having any residual effect on edible meat (Hashemi and Davoodi, 2010 (Subapriya and Nagini, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that inclusion of HFA in broiler diet improves performance, enhances feed utilization and promotes gut health of broiler without having any residual effect on edible meat (Hashemi and Davoodi, 2010 (Subapriya and Nagini, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…All parts of the plant -leaves, flowers, seeds, fruits, roots and bark -have been traditionally used for the treatment of inflammation, infections, fever, skin diseases and dental disorders (Subapriya & Nagini, 2005). A study recorded the properties of 150 triterpenoids from A. indica leaves (Akhila & Rani, 1999).…”
Section: Main Authormentioning
confidence: 99%
“…Every part of the tree has been used in traditional medicine for various human ailments [2][3][4][5][6]. Myriad of secondary metabolites [7] from different parts of the tree have been found to be effective on a wide spectrum of diseases, including dermatophytosis. In the period of Harappa culture around 4500 years back neem was used in medical treatment [8].…”
Section: Introductionmentioning
confidence: 99%